Hubungan Antara Kebiasaan Membaca, Penguasaan Kosakata dan Ketrampilan Membaca Kelas VIII SMP Negeri 1 Karanganyar - Farro Durrotul Qorri’aina; Sujoko Sujoko; Ngadiso Ngadiso (Teknodika, 2018)
This study is aimed to find out the correlation between: (1) reading habit and reading skills of the second grade students of SMP Negeri 1 Karanganyar; (2) vocabulary mastery and reading skills of the second grade of SMP Negeri 1 Karanganyar; (3) reading habit and vocabulary mastery simultaneously and reading skills of the second grade of SMP Negeri 1 Karanganyar. The study focused on English lesson material that was involved reading activities. The study belongs to correlational study. The population was all of the second grade students of SMP Negeri 1 Karanganyar. The sample was 24 students that were selected by using cluster random sampling technique. The instruments used to collect the data were tests and questionnaire. The questionnaire was used to collect the data of reading habit. The techniques used to analyze the data were Simple and Multiple Linear Regression and Correlation. The result of the study show that (1) there is a positive correlation between students’ reading habit and students’ reading skill that can be showed r-count is more than rtable (2.553>1.717); (2) there is a positive correlation between students’ vocabulary mastery and students’ reading skills that can be showed r-count is more that r-table (2.120>1.717); (3) there is a positive correlation between students’ reading habit and vocabulary mastery simultaneously and students’ reading skills that can be showed fcount is more that f-table (6.266>3.467). With regard to the result of the study, it can be concluded that positive correlation between reading habit and vocabulary mastery and reading skills indicates that both reading habit and vocabulary mastery could support and ultimately give contribution to reading skills. Hence, students’ reading and vocabulary mastery need to be considered in the teaching and learning activities of reading.